2003
DOI: 10.1080/0144619032000049737
|View full text |Cite
|
Sign up to set email alerts
|

Redefining performance measures for construction project managers: an empirical evaluation

Abstract: Traditional success criteria for construction projects centre on the achievement of cost, programme and quality targets. In this paper, it is argued that these simple measures are too crude to be used for gauging managers' performance in the context of today's construction project environment, as many variables outside of the manager's control can impact on outturn performance and the demands on project managers are far broader than in the past. It is argued that the industry needs to define more appropriate p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(81 citation statements)
references
References 14 publications
1
72
0
1
Order By: Relevance
“…This way, the level of cooperation on a construction project can be monitored on a consistent basis and strategies, such as those considered in the current study, can then be implemented if a low level of or significant reduction in cooperation is observed. The inclusion of such scales, which measure performance as the behavior (not its antecedents or consequences) in performance monitoring questionnaires will answer the call for more direct and balanced human performance criteria, which temporally precede and are necessary for achieving the more demanding, 'harder' outturn project performance criteria (Dainty et al, 2003;Anvuur and Kumaraswamy, 2008).…”
Section: Practical Implicationsmentioning
confidence: 99%
“…This way, the level of cooperation on a construction project can be monitored on a consistent basis and strategies, such as those considered in the current study, can then be implemented if a low level of or significant reduction in cooperation is observed. The inclusion of such scales, which measure performance as the behavior (not its antecedents or consequences) in performance monitoring questionnaires will answer the call for more direct and balanced human performance criteria, which temporally precede and are necessary for achieving the more demanding, 'harder' outturn project performance criteria (Dainty et al, 2003;Anvuur and Kumaraswamy, 2008).…”
Section: Practical Implicationsmentioning
confidence: 99%
“…As a result, the performance of the construction industry as a whole tends to be scarce (Costa et al, 2006). Thus, a holistic view of performance measurements in the realm of multifaceted construction projects has been highlighted recently (Dainty et al, 2003;Chan and Chan, 2004;Leung et al, 2004;NzekweExcel, 2012;Lehtiranta et al, 2012).…”
Section: Performance Measurement and Benchmarkingmentioning
confidence: 99%
“…Also with the help of KPIs, companies can identify the best practices for developing their operations (CCI, 2004). However, hard measures have also been criticized for that they are too simple to measure the complex construction project environment (Dainty et al, 2003).…”
Section: Performance Measurement and Benchmarkingmentioning
confidence: 99%
“…They are productivity, quality, leadership, communication competence, administrative competence, effort, interpersonal competence, job knowledge, compliance with or acceptance of authority, and overall job performance. Dainty et al (2003), based on their logistic regression analysis, found 12 competencies helping to distinguish between superior and average performers. These competencies are achievement orientation, initiative, information seeking, focus on client's needs, impact and influence, directiveness, teamwork and cooperation, team leadership, analytical thinking, conceptual thinking, self-control, and flexibility Performance consists of seven dimensions: effectiveness, efficiency, quality, productivity, quality of work life, innovation, and profitability (Sink 1985).…”
Section: Performance Parametersmentioning
confidence: 99%